Susceptibility of Angiostrongylus cantonensis Larvae to Anthelmintic Drugs - Roquini, Daniel B.; Silva, Gabriel L.; Ferreira, Leonardo L. G.; Andricopulo, Adriano D.; Wilairatana, Polrat; De Moraes, Josué (Frontiers in Pharmacology, 2022)
Human helminthiasis affects approximately one in five people in the world and disproportionally affects the poorest and most deprived communities. Human angiostrongyliasis, caused by nematode Angiostrongylus cantonensis, is a neglected emerging disease with escalating importance worldwide. Chemotherapy is the main control method for helminthiasis, but the therapeutic arsenal is limited. This study aimed to evaluate the antiparasitic and molecular properties of the major available anthelminthic drugs against A. cantonensis in vitro. The first-stage larvae (L1), isolated from feces of an A. cantonensis-infected rat, were exposed to a set of 12 anthelminthic drugs in vitro. The larvae were monitored, and the concentration- and time-dependent viability alterations were determined. From 12 anthelminthic drugs, six (ivermectin, salamectin, moxidectin, pyrantel pamoate, albendazole and levamisole) were identified to affect the viability of A. cantonensis. The macrocyclic lactones (ivermectin, salamectin, moxidectin) and the imidazothiazole levamisole, were the most effective drugs, with IC50 ranging from 2.2 to 2.9 µM and a rapid onset of action. Albendazole, the most widely used anthelmintic in humans, had a slower onset of action, but a IC50 of 11.3 µM was achieved within 24 h. Molecular properties studies suggest that a less lipophilic character and low molecular weight could be favorable for the biological activity of the non-macrocyclic molecules. Collectively, our study revealed that macrocyclic lactones, levamisole, pyrantel pamoate, and albendazole are important anthelminthic agents against A. cantonensis. The results of this in vitro study also suggest that A. cantonensis L1 may be a particularly sensitive and useful model for anthelminthic studies.